1987
DOI: 10.1099/00221287-133-12-3319
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of PAGE Protein Patterns and the Taxonomic Relationships within the 'Mycoplasma mycoides Cluster'

Abstract: Twenty-six isolates belonging to the 'Mycoplasma mycoides cluster' have been characterized by one-dimensional SDS-PAGE of their cellular proteins. A numerical classification based on the resulting patterns and using a correlation coefficient revealed four distinct phenons at a similarity (S) level of 70%, comprising: (a) bovine group 7 strains; (b) M. capricolum and F38-like strains; (c) M. mycoides subsp. capri and LC strains ('subsp. mycoides'); (d) M. mycoides subsp. mycoides (SC). At the 75% S level, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 9 publications
6
39
0
2
Order By: Relevance
“…MmmSC, the agent of CBPP, belongs to the so-called Mycoplasma mycoides cluster, which includes six mycoplasma subspecies and groups of strains that are closely related from both a phenotypic and a genetic point of view [9,10]. The organisms most closely related to MmmSC are M. mycoides subsp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MmmSC, the agent of CBPP, belongs to the so-called Mycoplasma mycoides cluster, which includes six mycoplasma subspecies and groups of strains that are closely related from both a phenotypic and a genetic point of view [9,10]. The organisms most closely related to MmmSC are M. mycoides subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation of the strains belonging to these three taxons is difficult when relying only on the standard growth inhibition technique. Concerning intra-species polymorphism, comparative studies by SDS-PAGE have already shown that strain variability within MmmSC is much more limited than within MmmLC and Mmc [9]. Although MmmSC is thought to be a very homogeneous taxon, previous studies have shown that MmmSC strains could be differentiated using molecular typing assays.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small number of biochemical or physiological properties available in Mycoplasmas, the definition of species has been based mainly on serological methods. But classifying the members of M. mycoides cluster has always been problematic: (i) Extensive and complex cross-reactions occur between subspecies or types, and acute antigenic identification of CBPP and CCPP agents has been achieved only through the use of specific monoclonal antibodies [4,32]; (ii) High antigenic heterogeneity within some types or subspecies (MmmLC, Mcc) hampers identification [6,18,27]; (iii) The definitive taxonomy of the M. mycoides cluster has not yet been established and discrepancies have recently appeared between their taxonomy and phylogeny. Msp7 strain PG50 produces significant cross-reactions with Mccp and, to some extent, with MmmSC [13,27], and should be phylogenetically included as a subspecies of the M. capricolum species [1,14,26,33].…”
Section: Introductionmentioning
confidence: 99%
“…capri and M. mycoides subsp. mycoides LC seem to represent different serovars rather than different subspecies [4,15,16,18,21,24,27,30,32,35]. This inability to distinguish these two organisms has been debated by the International Committee on Systematics of Prokaryotes -Subcommittee on the Taxonomy of Mollicutes, and it was suggested that an additional comparative analysis was required to definitively put an end to the inquiry about the relationship between these two mycoplasmas.…”
Section: Discussionmentioning
confidence: 99%
“…mycoides LC is reported to cause a pattern of diseases similar to those induced by M. mycoides subsp. capri in goats, including mastitis, keratoconjunctivitis, polyarthritis, pneumonia and septi-numerical analysis of one-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) protein patterns [4,16], by two-dimensional PAGE protein patterns [21,27], as well as by serological analysis [18]. A DNA probe based on a randomly selected genomic fragment was developed for the differentiation of the different members of the "mycoides cluster".…”
Section: Introductionmentioning
confidence: 99%